Jelenia Góra jako garnizon wojskowy - Stachula, Adolf (Jelenia Góra as A Military Base, 2006)
The article is an attempt to synthesyze the history of the town, as related to permanent stationing of military forces during the recent two centuries. It became possible to station the troops when the municipal authorities bought and repaired barrack properties. Social development and technical improvements as well as the two world wars made it necessary to develop the army structure as well as new garrisons. Most military objects were established before and during the First World War - this refers especially to military hospitals. Between the two world wars, two new garrisons were built to house Wehrmacht, one in Sudecka Str. and the other in Grunwaldzka Str. After 1945, some objects were transferred for the use of the population of Jelenia Góra. What remained in military use was primarily the two barrack complexes in Sudecka and Grunwaldzka Str., where for the nearly 60 years some troops of Polish Army were stationed until they were disbanded in 2004. Since then Jelenia Góra has lost its status of a military garrison town.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 444-451